2012
DOI: 10.1186/1471-2407-12-521
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Snail is associated with lymph node metastasis and poor prognosis in patients with gastric cancer

Abstract: BackgroundEpithelial–mesenchymal transition (EMT) plays a significant role in tumor progression and invasion. Snail is a known regulator of EMT in various malignant tumors. This study investigated the role of Snail in gastric cancer.MethodsWe examined the effects of silenced or overexpressed Snail using lenti-viral constructs in gastric cancer cells. Immunohistochemical analysis of tissue microarrays from 314 patients with gastric adenocarcinoma (GC) was used to determine Snail’s clinicopathological and progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 29 publications
4
72
0
Order By: Relevance
“…2A and B). The zinc finger-containing proteins Snail and Slug and the helix-loop-helix transcription factor Twist repress E-cadherin expression and induce EMT in gastric cancer [24-26]. We thus assessed the expression levels of the above E-cadherin regulators in RhoGDI2-overexpressing SNU-484 cells to determine the effect of RhoGDI2.…”
Section: Resultsmentioning
confidence: 99%
“…2A and B). The zinc finger-containing proteins Snail and Slug and the helix-loop-helix transcription factor Twist repress E-cadherin expression and induce EMT in gastric cancer [24-26]. We thus assessed the expression levels of the above E-cadherin regulators in RhoGDI2-overexpressing SNU-484 cells to determine the effect of RhoGDI2.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the involvement of NF-κB-Snail-E-cadherin axis or CCR7 pathway in induction of EMT through upregulating Snail signaling proved in GC both implied the decisive role of Snail explicitly (25,26). Furthermore, Shin et al (27) reported that Snail could be a prognostic predictor of gastric cancer due to its strong interrelationship with tumor progression, lymph node metastasis, lymphovascular or perineural invasion. Twist protein is a member of the basic/helix-loop-helix transcription factor family and binds selectively to the E-box consensus sequence to regulate target genes such as E-cadherin (28).…”
Section: Epithelial-mesenchymal Transition and Gastric Cancermentioning
confidence: 99%
“…12 Intriguingly, increased Snail expression is detected in metastatic gastric-cancer cells and is required for EMT and gastric-cancer cells migration and invasion. 13 WAVE3, a member of the WASP (Wiskott-Aldrich syndrome protein)/WAVE actin cytoskeleton remodeling family of proteins, is critical for the motility, migration and invasive properties of cancer cells. 14 More importantly, Taylor et al 15 reported in 2013 that WAVE3 expression is required in mediating the initiation of EMT programs stimulated by TGF-β.…”
Section: Introductionmentioning
confidence: 99%